BAND HETEROTOPIA - Alam, MS; Naila, N (Journal of Ayub Medical College Abbottabad, 2010)
Band heterotopias are one of the rarest groups of congenital disorder that result in variable degree of structural abnormality of brain parenchyma. Band of heterotopic neurons result from a congenital or acquired deficiency of the neuronal migration.1 MRI is the examination of choice for demonstrating these abnormalities because of the superb gray vs. white matter differentiation, detail of cortical anatomy and ease of multiplanar imaging.2 We report a case of band heterotopia that showed a bilateral band of gray matter in deep white matter best demonstrated on T2 Wt. and FLAIR images. Keywords: Heterotopia, congenital, deep white matter